Crisis Management Principles, Roles and Application - Yi, Carine (IntechOpen, 2023)
Crisis Management - Principles, Roles and Application provides a comprehensive overview of crisis management in business, management, and economics. Chapters address such topics as collaborative crisis management, social media and crisis management, the role of public service organizations in emergency and crisis management, and more. This volume is a valuable resource for opening new research paths for further novel developments in the field of crisis management.